2011
DOI: 10.1002/cphc.201001010
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Red Sites and Energy Transfer Rates in Single MEH‐PPV Chains at Low Temperature

Abstract: Single poly[2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) molecules dispersed in thin poly(methylmethacrylate) films have been investigated by fluorescence emission, excitation and time-resolved spectroscopy at 1.2 K. For the molecular weight studied (∼200 kDa) a bimodal distribution of emission maxima is observed. Based on a comparison of the spectroscopic properties of blue and red sites and on polarisation-resolved measurements, we argue in agreement with recent quantum-chemical calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 85 publications
(192 reference statements)
7
50
0
Order By: Relevance
“…22,24,26,27,30,59,60 It was suggested that photoluminescence decay in isolated chains is mono-exponential with characteristic time scales between 0.4 and 1.2 ns, while non-exponential relaxation was observed in presence of aggregation, 24,27 in films, 17,61,62 and in collapsed MEH-PPV chains. 23,63 All the aforementioned configurations are characterized by a strong reduction in the photoluminescence quantum yield, which is ascribed to the formation of non-emissive interchain species.…”
Section: A Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24,26,27,30,59,60 It was suggested that photoluminescence decay in isolated chains is mono-exponential with characteristic time scales between 0.4 and 1.2 ns, while non-exponential relaxation was observed in presence of aggregation, 24,27 in films, 17,61,62 and in collapsed MEH-PPV chains. 23,63 All the aforementioned configurations are characterized by a strong reduction in the photoluminescence quantum yield, which is ascribed to the formation of non-emissive interchain species.…”
Section: A Population Dynamicsmentioning
confidence: 99%
“…The red sites have been repeatedly ascribed to planarized segments characterized by an increased conjugation length compared to the blue sites. 25,26 It was also suggested that the formation of the red sites might be related to aggregation. 22,27 Recent studies showed that concentrated solutions of MEH-PPV in 2-methyltetrahydrofuran (MeTHF) undergo a phase transition from a coiled conformation ("blue phase"), characteristic of room temperature, to an aggregated and planarized phase at low temperatures ("red phase"), characterized by very long conjugation length.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37] Recent work by three of us 27 showed that MEH-PPV chains dissolved in methyltetrahydrofuran (MeTHF) undergo a phase transition at approximately 200 K. Above this temperature, the polymer exists in a disordered coil morphology referred to as the blue phase. As the solution is cooled through the transition temperature, the polymer assembles into aggregates (the "red-phase") in which polymer chains are substantially elongated causing a red shift of the absorption and fluorescence spectra relative to the spectra of more disordered chains.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral blue-shift upon charge injection 11 suggests that formation of the quencher occurs predominantly, but not always, on low-energy chromophores. 29 The quenching of the low-energy chromophores also over-compensates a possible red-shift in emission of the remaining chromophores due to the Stark effect, which was shown to be in the order of 2nm for an electric field of 300kV/cm. 11 The electric field of a single charge at a distance of 5-10nm is approx.…”
mentioning
confidence: 99%